COVID-19 and Pediatric Lung Disease: A South African Tertiary Center Experience - Gray, Diane M.; Davies, Mary-Ann; Githinji, Leah; Levin, Michael; Mapani, Muntanga; Nowalaza, Zandiswa; Washaya, Norbertta; Yassin, Aamir; Zampoli, Marco; Zar, Heather J.; Vanker, Aneesa (Frontiers in Pediatrics, 2021)
The COVID-19 pandemic led to rapid global spread with far-reaching impacts on health-care systems. Whilst pediatric data consistently shows a milder disease course, chronic lung disease has been identified as a risk factor for hospitalization and severe disease. In Africa, comprised predominantly of low middle-income countries (LMIC), the additional burden of HIV, tuberculosis, malnutrition and overcrowding is high and further impacts health risk. This paper reviewed the literature on COVID-19 and chronic lung disease in children and provides our experience from an African pediatric pulmonary center in Cape Town, South Africa. South African epidemiological data confirms a low burden of severe disease with children <18 years comprising 8% of all diagnosed cases and 3% of all COVID-19 admissions. A decrease in hospital admission for other viral lower respiratory tract infections was found. While the pulmonology service manages children with a wide range of chronic respiratory conditions including bronchiectasis, cystic fibrosis, asthma and interstitial lung disease, no significant increase in COVID-19 admissions were noted and in those who developed COVID-19, the disease course was not severe. Current evidence suggests that pre-existing respiratory disease in children does not appear to be a significant risk factor for severe COVID-19. Longitudinal data are still needed to assess risk in children with immunosuppression and interstitial lung diseases. The indirect impacts of the pandemic response on child respiratory health are notable and still likely to be fully realized and quantified. Ensuring children have access to full preventive and care services during this time is priority.